Can smoking duration alone replace pack-years to predict the risk of smoking-related oncogenic mutations in non-small cell lung cancer? A cross-sectional study in Japan. Issue 9 (9th September 2020) - Ogawa, Koichi; Koh, Yasuhiro; Kaneda, Hiroyasu; Izumi, Motohiro; Matsumoto, Yoshiya; Sawa, Kenji; Fukui, Mitsuru; Taniguchi, Yoshihiko; Yoshimoto, Naoki; Tamiya, Akihiro; Ando, Masahiko; Kubo, Akihito; et al.
Abstract : Objective: To investigate whether smoking duration alone can replace pack-years to predict the risk of oncogenic mutations in non-small cell lung cancer (NSCLC). Design: A cross-sectional study using the baseline dataset from the Japan Molecular Epidemiology for Lung Cancer Study. Setting: Forty-three medical institutions nationwide in Japan. Participants: From July 2012 to December 2013, 957 patients with newly diagnosed stage I–IIIB NSCLC who underwent surgery were enrolled, and molecular analyses were performed on 876 samples (from 441 ever-smokers and 435 never-smokers). Main outcomes measured: We calculated the area under the receiver operating characteristic curve (AUC) values using logistic regression to compare between the predictive values of smoking duration and pack-years for mutational frequencies in the v-Ki-ras2 Kirsten rat sarcoma ( KRAS ), tumour suppressor p53 ( TP53 ), and epidermal growth factor receptor ( EGFR ) genes and for cytosine-to-adenine base substitution (C>A). Results: For predicting KRAS mutations, the AUC values for smoking duration and pack-years were 0.746 (95% CI 0.682 to 0.800) and 0.759 (95% CI 0.700 to 0.810), respectively (p=0.058). For predicting KRAS mutations in smokers, the AUC values for smoking duration and pack-years were 0.772 (95% CI 0.697 to 0.833) and 0.787 (95% CI 0.714 to 0.845), respectively (p=0.036). There were no significant differences between the AUC values for smoking duration and pack-years in terms of predicting TP53 and EGFR mutations and C>A. Pack-years was a significantly better predictor of KRAS mutations than smoking duration. Conclusion: Smoking duration was not significantly different from pack-years in predicting the likelihood of smoking-related gene mutations. Given the recall bias in obtaining smoking information, smoking duration alone should be considered for further investigation as a simpler alternative to pack-years.